Inventing Voice of Identity through L2 Poetry Writing: A Construct of Mindfulness-Based Strategy in Remote Learning - Piscayanti, Kadek Sonia; Yuliasri, Issy (Language Circle: Journal of Language and Literature, 2021)
Voice of identity can be found in an expressive writing such as poetry writing. In l2 learning context, poetry is a medium to learn a new language in a creative way. Language is developed through mindfulness and creativity. As language develops, l2 learners make use of their sensitivity to language and create or produce the language that represents the voice of identity themselves. This article focuses on how l2 poetry writing can invent voice of identity in the l2 learners by using the construct of mindfulness-based strategy. In the pandemic context where offline education is not possible, mindfulness-based strategy is best implemented in l2 remote learning since it has four main principles in language learning such as finding novelty in learning, being sensitive to context, actively engaged in the present moment, and stimulate opennes and multiperspectives. By online learning, poetry is taught with mindfulness concepts and they are guided mindfully on how they become language learners creatively and effectively by writing their poetry about their life during the pandemic. The data collected are poetry and reflection diary and analyzed through the construct of poetry in mindfulness framework. The results indicated that poetry writing can represent voice of l2 learner’s identity; their new perspectives of the world, reflection and sensitivity to context, choices of life, present moment engagement, opennes and multiperspectives